POLA KOMUNIKASI ORGANISASI DALAM MENINGKATKAN KINERJA PEGAWAI PADA DINAS PENDIDIKAN KABUPATEN LUWU - Risnayanti, Risnayanti; Ahdan, Ahdan; Muliadi, Muliadi (UNIVERSITAS MUSLIM INDONESIA, 2022)
The purpose of this study was to determine the pattern of organizational communication in improving employee performance at the Luwu District Education office and to descrite the employee performance at the Luwu District Education Office. The results of this study indicate that the communication that takes place at the Luwu District Education office uses a model or from of formal communication. As for the performance of employees at the Luwu Regency Education Office that performance is the result of work both in quality and quantity that has been achieved by employees, in carrying out their duties in accordance with the responsibilities given by the results of their work are adjusted to the work expected by the organization, and the results of